TECTONIC CRUSTAL MOVEMENTS BASED ON STRAIN DATA - Karmaleeva R.M.; Latynina L.A. (My University, 1992)
Continuous measurements of horizontal crustal deformations are performed, as a rule with the help of the rod strain gauges with the based length of about 20 m. The time stability of these instruments is 10−7. The problem is whether these instruments can be used to study tectonics in a certain region, or they can record only local processes in situ.This paper deals with the results of measurements taken in two testing areas in the C.T.S. According to the data of the strain measuring stations in the Garm testing area, which are equipped in some cases with parallel instruments, the average rate of rock compression amounts to 15 1o−7 year. The agreement between these data, the results of repeated geodetic measurements and the general ideas the regional evolution bears witness to the tectonic nature of reported deformation. The measurement results, obtained at the stations in the Alma Ata testing area, display a different picture to the one obtained in Garm, where either alternating deformation (the Talgar station), or expansion is recorded.A possibility of applying the deformation measuring method is considered for the study of recent tectonics.